Dying to sleep [videorecording (DVD)] - Dylan, Paris; Roberts, Eric, 1956-; Sheridan, Dave, 1969-; Baldesarra, Victoria; Dickens, Charles, 1812-1870 (Blood House Films, 2023)
Mary, desperate to find a cure for her chronic, terrifying nightmares, takes a leap of faith on a reclusive Holistic Doctor, but as her clarity sharpens, Mary unearths the frightening mystery behind his obscure methods.